+0

# [(2x+1)/3]+[(5x-2)/2]-[(3x-3)/5]=2

0
356
4

[(2x+1)/3]+[(5x-2)/2]-[(3x-3)/5]=2

Guest Feb 8, 2016

#2
+91039
+15

Hi Rarinstraw,

This is the BEST way to do it :)

$$\frac{(2x+1)}{3}+\frac{(5x-2)}{2}-\frac{(3x-3)}{5}=2 \\ \mbox{Multiply through by the lowest common multiple - that is 30}\\ \frac{30(2x+1)}{3}+\frac{30(5x-2)}{2}-\frac{30(3x-3)}{5}=60 \\ \frac{10(2x+1)}{1}+\frac{15(5x-2)}{1}-\frac{6(3x-3)}{1}=60 \\ 10(2x+1)+15(5x-2)-6(3x-3)=60 \\ \mbox{See that got rid of all the fractions :)}\\ 20x+10+75x-30-18x+18=60\\ 20x+75x-18x+18+10-30=60\\ 77x-2=60\\ 77x=62\\ x=\frac{62}{77}\\$$

Melody  Feb 8, 2016
Sort:

#1
+5197
+3

2/3x + 1/3 + 2 1/2x - 1 - 3/5x - 3/5 =2

Combine like terms.

The decimals are approximate, the numbers would have repeated for ages otherwise.

2.57x - 1.26 = 2

2.57x=3.26

2.57x=3.26 = x=(326/257)

rarinstraw1195  Feb 8, 2016
#2
+91039
+15

Hi Rarinstraw,

This is the BEST way to do it :)

$$\frac{(2x+1)}{3}+\frac{(5x-2)}{2}-\frac{(3x-3)}{5}=2 \\ \mbox{Multiply through by the lowest common multiple - that is 30}\\ \frac{30(2x+1)}{3}+\frac{30(5x-2)}{2}-\frac{30(3x-3)}{5}=60 \\ \frac{10(2x+1)}{1}+\frac{15(5x-2)}{1}-\frac{6(3x-3)}{1}=60 \\ 10(2x+1)+15(5x-2)-6(3x-3)=60 \\ \mbox{See that got rid of all the fractions :)}\\ 20x+10+75x-30-18x+18=60\\ 20x+75x-18x+18+10-30=60\\ 77x-2=60\\ 77x=62\\ x=\frac{62}{77}\\$$

Melody  Feb 8, 2016
#3
+5197
0

Looks a whole lot easier! Good job Melody!

rarinstraw1195  Feb 8, 2016
#4
+91039
0

Thanks rarinstraw :)

Melody  Feb 9, 2016

### 14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details